2013
DOI: 10.1093/carcin/bgt229
|View full text |Cite
|
Sign up to set email alerts
|

GPR48, a poor prognostic factor, promotes tumor metastasis and activates β-catenin/TCF signaling in colorectal cancer

et al.

Abstract: G-protein-coupled receptor 48 (GPR48) is an orphan receptor belonging to the G-protein-coupled receptors family, which plays an important role in the development of various organs and cancer development and progression such as gastric cancer and colorectal cancer (CRC). However, the prognostic value of GPR48 expression in patients with CRC has not been reported. In this study, we observed that GPR48 was overexpressed in primary CRC and metastatic lymph nodes and closely correlated with tumor invasion and metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 47 publications
4
44
1
Order By: Relevance
“…4,5 These results are not surprising, because GPCRs have the ability to use alternative For 47 and it is likely that these 2 GPCRs regulate distinct functional programs downstream of b-catenin through their respective signaling cascade in colon cancer. Furthermore, using clinically available Cox inhibitors, we and others have previously shown that inhibition of Cox suppresses b-catenin activation and has a profound effect on LSC functions in AML initiated by MLL-AF9 or AML1-ETO.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…4,5 These results are not surprising, because GPCRs have the ability to use alternative For 47 and it is likely that these 2 GPCRs regulate distinct functional programs downstream of b-catenin through their respective signaling cascade in colon cancer. Furthermore, using clinically available Cox inhibitors, we and others have previously shown that inhibition of Cox suppresses b-catenin activation and has a profound effect on LSC functions in AML initiated by MLL-AF9 or AML1-ETO.…”
Section: Discussionmentioning
confidence: 95%
“…G protein-coupled receptors (GPCRs), the largest family of cell-surface molecules with key roles in transmitting signals to downstream effectors, have emerged as crucial players in promoting tumor growth and metastasis 1,[4][5][6][7][8] and represent one of the most important drug targets in pharmaceutical development. 9,10 Recent evidence indicates that GPCRs are active in various cancer cell lines and primary patient samples, 7,8 and that oncogenic GPCRs augment activation of b-catenin signaling in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of the Wnt/β-catenin and Ras oncogene by P21-activated kinase 1 increases the progression of CRC and enhances survival by the stimulation of hypoxia-inducible factor 1α and β-catenin (19). In another study, Wu et al (20) showed that β-catenin increased T-cell factor 4 (TCF4) transcription activity and expression of its target genes, including cyclin D1 and c-Myc, in CRC cells. Correlation analysis showed that β-catenin expression in CRC tissues was positively associated with c-Myc expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of skin and prostate, LGR4 promotes tumorigenesis by modulating MEK/ERK and Wnt/β−catenin pathways and the PI3K/Akt cascade, respectively [98,99]. In colorectal cancer, LGR4 expression is markedly upregulated in moderately and poorly differentiated cells as well as at the tumor invasive front and in metastasis and it significantly correlates with nodal spread in gastric cancer [100][101][102]. Altogether, studies point LGR4 as a poor-prognosis factor.…”
Section: Prognostic Value Of Lgrsmentioning
confidence: 97%